1987
DOI: 10.1038/bjc.1987.169
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of placental alkaline phosphatase activity and cytokeratins in human HN-1 cells by butyrate, retinoic acid, catecholamines and histamine

Abstract: Summary The effects of butyrate and retinoic acid in combination with catecholamines or histamine on the HN-1 human head and neck squamous carcinoma cell line were investigated analysing cell proliferation, placental alkaline phosphatase (PLAP) activity, and relative cytokeratin content.Butyrate inhibited cell proliferation in agar, whereas retinoic acid induced a small inhibitory effect. Butyrate enhanced PLAP activity in a time related manner in contrast to retinoic acid, which had no significant effect. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…This growth inhibition was not just a cytotoxic effect, since MTS regrowth occurred when MTSs were rinsed free of RA and further cultured in RA-free medium (Sacks et al, 198913). Inhibition of MTS growth by RA agrees with reports of decreased proliferation by colony-forming efficiency for some SCC cell lines (Cline and Rice, 1983;Lotan et al, 1987;Sarkar and Das, 19881, while in other SCC cell lines proliferation is unaffected or even stimulated (Reiss et al, 1985;Lotan et al, 1987;Bijman et al, 1987).…”
Section: Discussionsupporting
confidence: 87%
“…This growth inhibition was not just a cytotoxic effect, since MTS regrowth occurred when MTSs were rinsed free of RA and further cultured in RA-free medium (Sacks et al, 198913). Inhibition of MTS growth by RA agrees with reports of decreased proliferation by colony-forming efficiency for some SCC cell lines (Cline and Rice, 1983;Lotan et al, 1987;Sarkar and Das, 19881, while in other SCC cell lines proliferation is unaffected or even stimulated (Reiss et al, 1985;Lotan et al, 1987;Bijman et al, 1987).…”
Section: Discussionsupporting
confidence: 87%
“…Thus ALP is not associated with melanogenesis and is not a general marker for differentiation in pigment cells. Endogenous ALP activity is extremely low in frozen tissues of normal melanocytes and benign melanocytic lesions (unpublished data), in the epidermis generally (Mier and van Rennes, 1982), and in melanomas (Nordenberg et al, 1987) and other tumors (Kim et al, 1980;Bijman et al, 1987). Therefore, the induction of ALP activity appears to occur randomly rather than as an intrinsic feature of differentiated phenotypes.…”
Section: Discussionmentioning
confidence: 91%
“…The converse, a reduction of proliferation due to PRO was also reported in the same era, for example Iwata, Kariya and Fujimoto showed that in a ciliated protozoan beta-adrenergic blockade, with PRO and other agents, was associated with a reduced rate of growth [97]. It has since been shown that PRO is able to inhibit the increase in cancer cell proliferation associated with catecholamines or isoproterenol in a number of cancer cell types [56, 98100]. …”
Section: Mechanisms Of Actionmentioning
confidence: 88%